2021
DOI: 10.1101/2021.08.25.457606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VTA-projecting cerebellar neurons mediate stress-dependent depression-like behavior

Abstract: Although cerebellar alterations have been implicated in mental depression, the exact contribution of the cerebellum to depressive symptoms remains to be elucidated. Here, we demonstrated the crucial role of cerebellar neurons projecting to the ventral tegmental area (VTA) in the chronic stress-induced development of depression-like behavior. The combination of adeno-associated virus-based circuit mapping and electrophysiological recording identified network connections from crus I to the VTA via the dentate nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Activity changes in these studies denote that the cerebellum has functional effects on the recorded brain regions through direct or indirect network connections. The direct functional connections have been verified by recording synaptic transmission from the neurons in target brain regions ex vivo , upon the photostimulation of channelrhodopsin-expressing DCN neuronal terminals ( Gornati et al, 2018 ; Xiao et al, 2018 ; Carta et al, 2019 ; Vaaga et al, 2020 ; Baek et al, 2021 ).…”
Section: Techniques To Unravel the Complexity Of Cerebellar Efferent Pathwaysmentioning
confidence: 95%
See 4 more Smart Citations
“…Activity changes in these studies denote that the cerebellum has functional effects on the recorded brain regions through direct or indirect network connections. The direct functional connections have been verified by recording synaptic transmission from the neurons in target brain regions ex vivo , upon the photostimulation of channelrhodopsin-expressing DCN neuronal terminals ( Gornati et al, 2018 ; Xiao et al, 2018 ; Carta et al, 2019 ; Vaaga et al, 2020 ; Baek et al, 2021 ).…”
Section: Techniques To Unravel the Complexity Of Cerebellar Efferent Pathwaysmentioning
confidence: 95%
“…Thus, even though anatomical connections from the DCN to the VTA appear to be minor, the VTA receives direct inputs from the DCN. It was originally suggested that projections originate from the FN and DN ( Parker et al, 2014 ), yet a study in preprint at this moment showed using adeno-associated virus (AAV)-based circuit mapping that the DCN-VTA connections were contralateral, and originated mainly from the DN and partly from the IPN ( Baek et al, 2021 ). The study also showed that among all the VTA regions, the dorsolateral posterior VTA was the main target of the DCN projections.…”
Section: New Lines Of Evidence On Efferent Pathways Associated With Non-motor Functions: Direct Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations